Unilamellar vesicles obtained by simply mixing dioctadecyldimethylammonium chloride and bromide with water - Feitosa, E.; Karlsson, G.; Edwards, K. (Elsevier B.V., 2006)
Optically clear dispersions of dioctadecyldimethylammonium bromide and chloride (DODAX, X = Br-, Cl-) in water can be obtained by simply mixing the amphiphiles at low concentrations (I mM) and at a temperature safely above the gel to liquid crystalline phase transition temperature (T-m approximate to 45-48 degrees C) of DODAX in water. Under these conditions, dynamic light scattering shows that, at room temperature, the dispersions contain two well-defined populations of large vesicles with average hydrodynamic radii (RH) of 80 and 337 nm for DODAB and of 69 and 247 nm for DODAC. Cryo-transmission electron microscopy (cryo-TEM) micrographs show that DODAX vesicles are unilamellar and polydisperse with apparent radius up to 800 nm. The vesicles are stable for at least I month according to the ageing time-dependence of the turbidity and molar absorption coefficient. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: dioctadecyldimethylammonium salts; unilamellar vesicles; Cationic vesicle; Cryo-TEM; light scattering; turbidity